Revolutionizing plant breeding: a historical perspective from cross-pollination to gene editing - T, Ugandhar; E, Komala.; Prasad. S, Shyam; D, Sammaiah.; Singh. M, Ghan; M, Narender; N, Gandhi (International Journal of Biological Research, 2024)
The history of plant breeding can be broadly divided into four eras: the Pre-Mendelian era (before 1900), the Mendelian era (1900-1920), the post-Mendelian era (1921-1950), and the Modern era (after 1950). Significant milestones include the release of the first hybrid maize varieties in 1961, the first sorghum hybrid (CSH-1) in 1964, the first bajra hybrid (HB-1) in 1965, and the first pigeon pea hybrid (ICPH-8) in 1991. Achieving a world with zero hunger requires a sustainable increase in food production and distribution and elimination of poverty. This goal demands scientific, logistical, and humanitarian approaches to ensure food security from farmers and breeders to policymakers and governments. Conventional breeding techniques alone are insufficient to meet the challenges posed by climate change, biotic and abiotic stress, and the growing global population projected to reach 10 billion by 2050. Novel plant breeding techniques, such as genome editing, speed breeding, and omics technology integration, offer precise, cost-effective, and less time-consuming solutions. These techniques enable the editing of agriculturally significant genes, promoting hybrid seed production, induced apomixis, and resistance to biotic and abiotic stress. Genome editing technologies have evolved, with CRISPR/Cas9 and its variants, base editing (BE), and prime editing (PE) playing pivotal roles in generating transgene-free plants. These advancements have significant implications for crop improvement, meeting food and nutrition security, and catering to regional preferences. Syngenta's initiative to open rights to CRISPR-based technologies through the Shoots by Syngenta platform exemplifies the collaborative efforts needed to drive agricultural innovation and sustainability. The review discusses the current regulatory regimes governing genome-edited crops, prospects of new tools such as DNA-free editing systems and nanotechnology, and their applicability in crop improvement. A multidisciplinary approach involving political, social, economic, and scientific stakeholders is essential for the successful adoption of genome editing technologies, which will ultimately make agriculture a lucrative profession and attract youth to the field.